Late Pleistocene–Holocene Palaeoenvironmental Evolution of the Makgadikgadi Basin, Central Kalahari, Botswana: New Evidence From Shallow Sediments and Ostracod Fauna - Franchi, Fulvio; Cavalazzi, Barbara; Evans, Mary; Filippidou, Sevasti; Mackay, Ruaraidh; Malaspina, Paolo; Mosekiemang, Goitse; Price, Alex; Rossi, Veronica (Frontiers in Ecology and Evolution, 2022)
The Makgadikgadi Basin in Botswana hosts a system of salt lakes, which developed from the Upper Pleistocene onwards due to gradual shrinking of the giant Lake Palaeo-Makgadikgadi. Stratigraphic and palaeoclimatic studies of this area are complicated by influence of several factors, such as a complex history of regional tectonic activities, as well as climatic changes coupled with dryland diagenetic processes. This lake, in the central Kalahari is the key to understand the climatic variability in the southern Africa in the Quaternary and holds important role for the evolution of numerous taxa, including our own. Here, detailed sedimentological analyses (grain size and major elements distribution) of shallow sediments from the Makgadikgadi Pans were combined with the first comprehensive study of the encountered ostracod fauna in order to establish trends in the environmental changes in the area from the Late Quaternary. Ostracod fossil assemblages from the cores of the Makgadikgadi Pans are dominated by the Limnocythere ssp., an opportunistic taxa commonly colonizing the littoral areas of shallow evaporative, ephemeral lakes, together with the subordinate occurrences of Sarcypridopsis ochracea, Sclerocypris cf. bicornis, Candonopsis spp. and Ilyocypris spp. The sediments from the pans show fluctuations in the Cl/K and Ca/Cl ratios, often in phase with the relative abundance of Limnocythere suggesting a cyclicity induced by changes of salinity and alkalinity in the water. This multi-proxy study of the cores collected from the pans suggests a Late Pleistocene shallow, playa lake environment with strongly alkaline water, interrupted by a prolonged drought with sustained aeolian conditions between ~16 and 2 ka BP. An increasing diversity of ostracod fauna in the top 20-30 cm of the cores indicates that a temporary shift toward higher humidity occurred around 2 – 1.5 ka BP and lasted through the Medieval Warm Period. This humid period was followed by an overall desiccation trend that started with the Little Ice Age and continues until the present day.